SPEECH ACTS ANALYSIS IN POSTS OF AL-JAZEERA'S ARABIC INSTAGRAM PAGE: تحليل أفعال الكلام في منشورات الصفحة العربية لقناة الجزيرة على منصة الإنستغرام - Alfarabi, Muhammad; Sudiarti, Sri; Mahendra, Ahdiyat (Journal of Arabic Language and Literature (ALLAIS), 2025)
This study investigates the use of speech acts in digital news discourse through an analytical examination of selected posts from the Arabic-language Instagram page of Al-Jazeera. Drawing on the theoretical framework of speech act theory as developed by Austin (1962) and Searle (1969), the research aims to identify the types and pragmatic functions of speech acts employed in visual-verbal posts related to political and social events. Using a descriptive-analytical method and qualitative content analysis, this study reveals that Al-Jazeera's Instagram posts do not merely perform an informative function; rather, they utilize a variety of speech act types—including assertives, directives, expressives, commissives, and declaratives—to construct meaning, influence perception, and guide public sentiment. The analysis highlights the strategic deployment of language in digital Arabic media to serve communicative intentions beyond mere news reporting. These findings contribute to a deeper understanding of how language operates as a pragmatic tool in shaping digital public discourse within Arabic media contexts.